Ecology of industrial pollution in China - Jingjing Yuan (Taylor & Francis Group, 2020)
Industrial development has brought China both opportunities and challenges since the reform and opening up in 1978. Spatial and temporal analysis showed that rapid industrialization has made eastern China under a more serious pollution stress. The most serious effects of industrial pollution were reflected in aquatic and soil ecosystem degradation, and damage can be observed from species, population, and community to ecosystem level. Public consciousness about contaminated sites rose from 2004 leading to greater efforts in ecological remediation, monitoring, and risk governance. Considerable efforts are still needed in expanding the extent and breadth of monitoring to explore where the greatest ecological risks lie and how to control them. Ecology of industrial pollution has become a popular discipline in China and will be further developed to help achieve the Sustainable Development Goals. Future research for a better ecological risk management should be focused on multi-media transfer and effects of mixed pollutants, mechanisms for clean energy and material flow, and integration of ecological risk with human health risk.